2019
DOI: 10.1021/acsmedchemlett.8b00508
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a JAK1/3 Inhibitor and Use of a Prodrug To Demonstrate Efficacy in a Model of Rheumatoid Arthritis

Abstract: The four members of the Janus family of nonreceptor tyrosine kinases play a significant role in immune function. The JAK family kinase inhibitor, tofacitinib 1, has been approved in the United States for use in rheumatoid arthritis (RA) patients. A number of JAK inhibitors with a variety of JAK family selectivity profiles are currently in clinical trials. Our goal was to identify inhibitors that were functionally selective for JAK1 and JAK3. Compound 22 was prepared with the desired functional selectivity prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…STATs are the phosphorylated downstream of JAKs, and these activated STAT dimers induce proinflammatory gene transcription inside the nucleus . As JAK/STAT signaling is generally involved in inflammation and autoimmune responses, researchers have actively developed JAK inhibitors for the treatment of inflammation and autoimmune-related diseases such as inflammatory bowel disease (IBD), rheumatoid arthritis (RA), and atopic dermatitis . Recent studies have indicated the potential of JAK inhibitors in the treatment of hepatic fibrosis. , The connective tissue growth factor (CTGF) is constantly expressed in activated hepatic stellate cells (HSCs) and modulates extracellular matrix production downstream of TGF-β in the fibrotic liver .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…STATs are the phosphorylated downstream of JAKs, and these activated STAT dimers induce proinflammatory gene transcription inside the nucleus . As JAK/STAT signaling is generally involved in inflammation and autoimmune responses, researchers have actively developed JAK inhibitors for the treatment of inflammation and autoimmune-related diseases such as inflammatory bowel disease (IBD), rheumatoid arthritis (RA), and atopic dermatitis . Recent studies have indicated the potential of JAK inhibitors in the treatment of hepatic fibrosis. , The connective tissue growth factor (CTGF) is constantly expressed in activated hepatic stellate cells (HSCs) and modulates extracellular matrix production downstream of TGF-β in the fibrotic liver .…”
Section: Introductionmentioning
confidence: 99%
“…NMR (400 MHz, methanol-d 4 ) δ 8.17 (s, 1H), 7.43−7.27 (m, 5H), 7.09 (d, J = 3.7 Hz, 1H),6.62 (d, J = 3 7. Hz, 1H), 4.45−4.37 (m, 1H), 3.81 (s, 2H), 2.97−2.87 (m, 2H), 2.87 (s, 3H), 2.88−2.78 (m, 2H), 2.27−2.14 (m, 2H), 1.94−1.84 (m, 2H), 1.80 (dd, J = 11.1, 7.4 Hz, 2H); 13 C NMR (100 MHz, methanol-d 4 ) δ 163.2, 141.3, 141.1, 135.6, 121.3, 121.0, 120.7, 120.1, 119.4, 118.6, 113.4, 97.2, 95.5, 93.8, 53.9, 46.9, 44.0, 41.9, 26.3, 25.3, 17.2, 14.6; HRMS (ESI, m/z) calcd for C 22 H 28 N 5 O [M + H] + 378.2288, found 378.2292.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There are promising inhibitors of various kinase enzymes (e. g., JAK, IRAK) which may be useful for treatment of diseases such as rheumatoid arthritis (Figure 1). [5] Moreover, these heterocycles were explored as blue light emitting fluorophores with highly promising properties. [6] Therefore, development of new synthetic routes to pyrrolo [1,2-b]pyridazines is an important task.…”
Section: Introductionmentioning
confidence: 99%
“…It has been well established that certain cytokines, for example, IL-2, can activate JAK1 or JAK3 kinase, which upon phosphorylation, binds STAT5 proteins and initiates the signaling pathways that regulate immune response and cell proliferation. To characterize JAK1/3 inhibitors functionally, we used cell-based assays that measure the inhibition of STAT5 phosphorylation and the cell proliferation of human primary T-cells when induced by IL-2. , Since the inhibition of JAK2 kinase is associated with anemia, thrombocytopenia, hyperlipidemia, and neutropenia, it is desirable to develop JAK1/3 inhibitors with selectivity over JAK2. It is also known that JAK2 kinase is involved in survival of erythroid precursor cells, which give rise to mature red blood cells, upon activation by erythropoietin (EPO); thus, a cell-based assay measuring survival of cultured human erythroid precursor cells (CHEP) was used to evaluate the activity for JAK2 inhibition. , …”
mentioning
confidence: 99%